Portuguese and Amsterdam Sephardic merchants in the tobacco trade Tierra Firme and Hispaniola in the early seventeenth century - Schreuder, Yda (Anthem Press, 2023)
Portuguese and Amsterdam Sephardic Merchants in the Tobacco Trade is a history of the role of Portuguese and Sephardic merchants in the tobacco industry and trade of Amsterdam. It focuses on the contraband trade with Tierra Firme and Hispaniola in the early seventeenth century as documented in the Engel Sluiter Historical Documents Collection. The intriguing question is, was tobacco traded and shipped alongside sugar or did the two trade flows have no relationship to each other? Whereas sugar cultivation was introduced to the Americas via the Atlantic Islands to Brazil and then transferred to the French and English Caribbean colonies, tobacco cultivation was indigenous to the Americas and was first introduced to Europe as mariners and merchants explored and engaged in mostly illegal trade along the Caribbean coast and estuaries of South America and the Caribbean Islands in the early seventeenth-century. Yda Schreuder highlights the impact of merchant networks that developed between Portuguese and Sephardic merchants in the course of the Eighty Years' War (1568-1648) between the Dutch Republic and the Spanish Habsburg Empire and uses the opportunity to explore the Engel Sluiter Historical Documents Collection available for research at the University of California, Berkeley Bancroft Library